2022
DOI: 10.3389/fnsyn.2022.925546
|View full text |Cite
|
Sign up to set email alerts
|

rTg(TauP301L)4510 mice exhibit increased VGlut1 in hippocampal presynaptic glutamatergic vesicles and increased extracellular glutamate release

Abstract: The molecular pathways that contribute to the onset of symptoms in tauopathy models, including Alzheimer’s disease (AD), are difficult to distinguish because multiple changes can happen simultaneously at different stages of disease progression. Understanding early synaptic alterations and their supporting molecular pathways is essential to develop better pharmacological targets to treat AD. Here, we focus on an early onset rTg(TauP301L)4510 tauopathy mouse model that exhibits hyperexcitability in hippocampal n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…We use our previously established cell culturing approach of hippocampal neurons cultured at PND5 that showed increased VGlut1 and glutamate release. 8 Here, we show that mitochondria morphology and structure change in P301L hippocampal neurons compared to hippocampal neurons from normal, non-transgenic litter mates (hereafter called tauP301L neg). We show that altered structure correlates with decreased basal P301L membrane potential.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…We use our previously established cell culturing approach of hippocampal neurons cultured at PND5 that showed increased VGlut1 and glutamate release. 8 Here, we show that mitochondria morphology and structure change in P301L hippocampal neurons compared to hippocampal neurons from normal, non-transgenic litter mates (hereafter called tauP301L neg). We show that altered structure correlates with decreased basal P301L membrane potential.…”
Section: Introductionmentioning
confidence: 78%
“…34 We then counted intensity spikes following our previously established approach of at least 1 standard deviation above noise level. 8 The number of identified release events were then aggregated and divided by the observation time to estimate release frequency. The intensity per vesicle was determined as the three frame average of the peak minus the three-frame average of baseline before release.…”
Section: La-sem Sample Preparation and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that Tau destabilization from MTs and its increased expression as a soluble MT-unbound protein, occurring at early stages of the disease, cause a significant increase in Tau nuclear levels, changing the expression of genes involved in synaptic transmission and leading to toxic hyperexcitability ( Siano et al, 2019b ). Accordingly, neuronal hyperexcitability, associated also with VGluT1 increase, has been identified as a hallmark of early AD pathology ( Ghatak et al, 2019 ; Siano et al, 2020 ; Taipala et al, 2022 ). The molecular mechanisms mediating this effect are still elusive.…”
Section: Discussionmentioning
confidence: 99%